2013
DOI: 10.4317/medoral.18732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of implant primary stability between maxillary edentulous ridges receiving intramembranous origin block grafts

Abstract: Purpose: The purposes of the present study were: to compare the resonance frequency analysis (RFA) values of implant placed in either ramus or calvaria block grafts; and to determine if implant diameter influences RFA implant stability quotient (ISQ) value. Material and Methods: This was a retrospective study that included 16 consecutives healthy patients treated with autogenous onlay block grafts for horizontal bone reconstruction in maxilla. Ten ramus and ten calvaria block graft treated patients were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The implant stability quotient should therefore be considered as a supplementary instrument to the clinical and radiographic examination [49]. Previous studies have demonstrated acceptable implant stability quotient following LARA with an autogenous bone block graft [50,51]. In the present systematic review, the implant stability quotient was solely assessed in one noncomparative study revealing high values at secondstage surgery following LARA with an autogenous tooth block graft [33].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The implant stability quotient should therefore be considered as a supplementary instrument to the clinical and radiographic examination [49]. Previous studies have demonstrated acceptable implant stability quotient following LARA with an autogenous bone block graft [50,51]. In the present systematic review, the implant stability quotient was solely assessed in one noncomparative study revealing high values at secondstage surgery following LARA with an autogenous tooth block graft [33].…”
Section: Discussionmentioning
confidence: 90%
“…The HSPIT is frequently used for defining a successful implant treatment outcome [50,51]. A clinical healthy peri-implant tissue is characterized by absence of erythema, bleeding on probing, swelling, and suppuration [52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the graft harvesting can be performed in the same surgery and under local anesthesia (25). On the contrary, iliac crest is an endochondral bone and it displays a more complete graft resorption during healing although this area can provide larger blocks than intraoral autogenous bone grafts (26). Despite of that, selected studies (18,19) showed similar results for bone resorption of ABGs.…”
Section: Discussionmentioning
confidence: 99%
“…26 RFA was shown to correlate with the amount of cortical bone height. 27,28 In this study, a marginal difference (P = .08) was found between both groups, favoring the ramus graft, therefore suggesting that both calvarial and ramus block grafts provided implants with similar initial stability. The fact that the bone density was similar between the two groups further supported the finding of similar RFA results between the two groups.…”
Section: Discussionmentioning
confidence: 54%